Numerical Study of Friction Behavior in Pneumatic Seal Cylinder - Nur Muhammad Malikul Adil; Muhammad Agus Kariem (Mesin, 2019)
This study presented the development of numerical model to investigate the behavior of the friction force between piston seal and cylinder bore. Two dimensional finite element model with constant velocity input was built. Numerical simulation showed the same trend as the experimental results from literature, with different of less than 5%. This comparison indicated that numerical model can be used for further simulation. At the end of the study, the friction force behavior for different stroke lengths were shown.